An assembling strategy for DNA cages with minimum strands. (August 2021) - Deng, Tao; Man, Zhengxing; Wang, Weilan
Graphical abstract: Highlights: Method and program for DNA cage design strategy. The strategy for assembling DNA cages with minimum strands. Some assembly mechanism laws for molecule design of DNA cages. Clarifying the minimum strands required to build a DNA polyhedron. Abstract: DNA polyhedra are artificial cage-like architectures based on interlocked and interlinked DNA double-strands. Using fewer strands to construct DNA cages shows an important role in the design of single-stranded DNA molecules. However, construction methods for DNA polyhedra from topological perspective remains not well understood. In this study, we theoretically propose an assembling strategy for DNA polyhedra with minimum strands based on computer algorithm. The results show that this efficient method could search DNA polyhedra with fewer strands faster. Our research provides new insights into design and synthesis for DNA polyhedra with required topological structures.